Supply chain management analysis in northern Thai SMEs - Uttapol Smutkupt (2018)
Supply Chain Management (SCM) is one of valuable techniques that can help organizations and their partners to improve their operations including lower inventories, lower costs, higher productivity, greater agility, shorter lead time, higher profits and greater customer loyalty. Today, many organizations around the world try to establish SCM with their partners. In Thailand, this situation is also the same. Therefore, an analysis of the selected SCM is considered to help organizations to improve their supply chain. This analysis will be focused only for Small and Medium Enterprises (SMEs) in the northern part of Thailand. To select the studied SCM for a case study, the Industry selection model (ISM) is formulated using multiple attribute decision making (MADM) to find the most important supply chain, tourism industry. In Thai tourism industry, there are at least five organizations, a hotel, a tour business, a car rental shop, a spa shop and a restaurant working together. After the review of the selected SCM, an evaluation of the selected supply chain is discovered. This evaluation technique is based on 62 related proposed questions in SCM. Within these 62 questions, they are categorized into 6 sections, Customer Information, Finance Information, Internal Process Data, Learning and Growth Data, Internal Supply Chain Data and Integrated Supply Chain Management. In each section, all questions must be answered with the score 1, 2, 3, 4 and 5. Then, this point is transformed to the question scores (between 0-1) by using desirability function. At this moment, the scores of each question and the scores of each section are also calculated. After that, the total score for each organization is created. Finally, the supply chain score is calculated by integrating the score of each organization in the supply chain together. The supply chain score shows how each organization that link together in the supply chain work. The high score mean they can work very well with each others whereas the low score mean they need to be improved. In our selected supply chain, tourism industry, the best score is only 0.636647 whereas the lowest score is 0.548326. As a result, if we need to implement SCM in full system in Northern Thai SMEs, further research to enhance our studied firm for supply chain management implementation is very important.